Avaliação de Usabilidade do SofiaFala: Melhorando a Tecnologia Assistiva para Terapias de Fala - Lembor, Victor Hugo da Silva; Macedo, Alessandra Alaniz (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2025.16300, 2025)
This paper presents a multifaceted usability evaluation protocol for SofiaFala-Fono, an assistive technology for speech therapists. Unlike traditional unimodal approaches, the protocol combines heuristic evaluation by HCI experts, usability testing with therapists, and affective response measurement (SAM questionnaire). This methodological triangulation offers a comprehensive assessment of effectiveness, efficiency, and user satisfaction, providing a replicable framework to support the development of more user-centered assistive technologies in speech therapy.